Fine oar mechanics - Kleshnev, V. (BioRow, 2021)
We continue the analysis of oar mechanics with two purposes here: 1) verify checksum of oar forces with the measured gate-pin forces; 2) relate oar forces with the propulsion of the rower-boat system.